Analisis Pengaruh Women Leadership dan Motivasi Kerja Terhadap Kinerja Karyawan pada The Right Two Wedding Organizer & Event Planner. - Sumadi, I Gede; Anna Maulidia; Ni Kadek Swandewi (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2025)
Effective leaders are capable of influencing and motivating their teams to achieve established goals. In modern business dynamics, numerous key factors influence employee performance, particularly in the context of women leadership. This research specifically analyzes the impact of women leadership and work motivation on employee performance at The Right Two Wedding Organizer & Event Planner, a company led by a woman. Utilizing a quantitative and qualitative approach, data was collected through questionnaires and interviews with supporting informants, comprising all permanent and freelance employees at The Right Two Wedding Organizer & Event Planner. A saturated sampling technique was employed. Data was analyzed using multiple linear regression with the aid of SPSS version 26, through validity, reliability, and classical assumption tests (normality, heteroscedasticity, and multicollinearity). The results of this study, via multiple linear regression analysis, indicate that women leadership and work motivation simultaneously have a positive and significant effect on employee performance.